Pioneer life in Kansas - Pincomb, Mary Josephine (My University, 1896)
Introduction: For the flourishing condition of our beloved state of Kansas we are greatly indebted to its earliest settlers, its pioneers. “Ad Aspera Per Aspera”, (“To the stars through difficulties”) has always been the motto for the people of Kansas, and they have succeeded in converting a broad expanse of uninhabited prairie into a thriving and prosperous state, whose citizens are free, liberty loving people, instead of hard bearded slave owners, as they might have been.
Citation: Pincomb, Mary Josephine. Pioneer life in Kansas. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Kansas; Pioneers; Liberty; Theses; Manuscripts (documents)